2002
DOI: 10.1002/syn.10133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging and social isolation on changes in brain monoamine turnover and biosynthesis of rats elicited by novelty stress

Abstract: Aging is a risk factor of human depression. Middle-aged or older men are vulnerable to adverse life events and an absence of social contact and easily become depressed. In the present study, we investigated the influence of aging on responses to life events in socially isolated conditions. We applied isolation-rearing (4 W) to two age groups, older (18 M) and younger (11 W), of male F344 rats that had been reared in a group and then examined responses to novelty stress (20 min). Changes in brain monoamines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 50 publications
1
28
1
2
Order By: Relevance
“…Whether a maintained number of 5-HT-IR cells in the dorsal raphé nucleus of FSL rats reflects a compensatory mechanism to counteract a possible age-related impairment of hippocampal 5-HT innervation is a matter of speculation, but it remains a heuristic possibility. Although agingassociated impairments in the serotonergic system have been reported for normal rats in several studies (Davidoff and Lolova, 1991;Maines et al, 1998;Miura et al, 2002), our results suggest that earlier and more pronounced alterations in the 5-HT system may take place in individuals with a genetic predisposition to depression.…”
Section: Discussioncontrasting
confidence: 65%
“…Whether a maintained number of 5-HT-IR cells in the dorsal raphé nucleus of FSL rats reflects a compensatory mechanism to counteract a possible age-related impairment of hippocampal 5-HT innervation is a matter of speculation, but it remains a heuristic possibility. Although agingassociated impairments in the serotonergic system have been reported for normal rats in several studies (Davidoff and Lolova, 1991;Maines et al, 1998;Miura et al, 2002), our results suggest that earlier and more pronounced alterations in the 5-HT system may take place in individuals with a genetic predisposition to depression.…”
Section: Discussioncontrasting
confidence: 65%
“…A variety of studies have revealed that the activation of the HPA-axis, as it occurs, for instance, during the separation from the mother or both parents (Gruss, Westphal, Luley, & Braun, 2006;Lehmann & Feldon, 2000) and other juvenile and adult stress paradigms (Kudielka & Kirschbaum, 2005), modulate monoaminergic systems in adult animals (Fuchs & Flugge, 2002) and also during development. For instance, rats which have been raised in social isolation display dramatically decreased dopamine metabolites (Miura, Qiao, & Ohta, 2002). This is in line with anatomical findings in degus and gerbils which were raised under socially deprived conditions and which as adolescents showed reduced densities of dopaminergic fiber innervation in some subregions of the prefrontal cortex (Braun, Lange, Metzger, & Poeggel, 2000;Winterfeld, Teuchert-Noodt, & Dawirs, 1998).…”
Section: Impact Of Early Emotional Experience On Synaptic Reorganizatmentioning
confidence: 66%
“…In the present study, the basal DA levels in male Wistar rats isolated from P28 to P85 are not different from age-matched group-reared controls. Unlike a great number of studies focusing on DA levels in the mPFC and NAc, relatively fewer works address the change of DA level in the AMY in social isolation model (Heidbreder et al 2000;Miura et al 2002). In isolationreared male Wistar rats (isolated from P21 to P105), the DA level in the AMY is reduced, yet the DA turnover is increased (Heidbreder et al 2000).…”
Section: Discussionmentioning
confidence: 97%